2014
DOI: 10.3892/or.2014.3566
|View full text |Cite
|
Sign up to set email alerts
|

Chelidonium majus L. extract induces apoptosis through caspase activity via MAPK-independent NF-κB signaling in human epidermoid carcinoma A431 cells

Abstract: Abstract. Chelidonium majus L. (C. majus L.) is known to possess certain biological properties such as anti-inflammatory, antimicrobial, antiviral and antitumor activities. We investigated the effects of C. majus L. extract on human epidermoid carcinoma A431 cells through multiple mechanisms, including induction of cell cycle arrest, activation of the caspase-dependent pathway, blocking of nuclear factor-κB (NF-κB) activation and involvement in the mitogen-activated protein kinase (MAPK) pathway. C. majus L. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…p38MAPK-dependent and p38MAPK-independent NF-kappaB signaling pathway was reported in some different types of cells [ 39 , 40 , 44 46 ]. Wang et al reported that focal adhesion kinase activates NF-kappaB via ERK1/2 and p38MAPK pathways in Aβ(25–35)-induced apoptosis of differentiated PC12 cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…p38MAPK-dependent and p38MAPK-independent NF-kappaB signaling pathway was reported in some different types of cells [ 39 , 40 , 44 46 ]. Wang et al reported that focal adhesion kinase activates NF-kappaB via ERK1/2 and p38MAPK pathways in Aβ(25–35)-induced apoptosis of differentiated PC12 cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CM showed an anti-angiogenesis effect that was dependent on decreased activity of migration, inhibition of VEGF and MMP-2,-9 and increase of TIMP release (KIM et al, 2011). Beside and Park et al (2015) found that, CM extract induce cell cycle arrest, activation of the caspase-3 dependent pathway, blocking of NF-κB activation as well as significantly decrease the mRNA levels of Bcl-2, survivin and increase Bax expression. Moreover, sanguinarine isolated from CM, suppresses NF-κB and sensitizes cancer cells to apoptosis by inducing ROS generation and activate TNF-related apoptosis-inducing ligand ( Gupta et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, CDK inhibitors bind with active CDK-cyclin complexes and cause cell cycle arrest, thereby exerting a tumor-suppressive role (Park et al, 2014). Moreover, studies have shown that 2 0 -4 0 -7 0trisubstituted isoflavones promote cell cycle arrest at G0/G1 and apoptosis in breast cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%